2017
DOI: 10.1002/hep.29310
|View full text |Cite
|
Sign up to set email alerts
|

Serum microcystin levels positively linked with risk of hepatocellular carcinoma: A case‐control study in southwest China

Abstract: We provide evidence that serum MC-LR was an independent risk factor for HCC in humans, with an obvious positive interaction with hepatitis B virus and alcohol but a negative interaction with aflatoxin. (Hepatology 2017;66:1519-1528).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
61
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 117 publications
(68 citation statements)
references
References 49 publications
(89 reference statements)
0
61
0
4
Order By: Relevance
“…While the conventional treatment technologies can eliminate intact toxic cyanobacterial cells effectively, these technologies have limited capability for removal of dissolved cyanobacterial toxins, which allows that these reach human populations via drinking water supplies in sufficiently high concentrations to cause adverse effects in the gastrointestinal system (Table 1). Chronic exposures to drinking water contaminated with cyanobacterial compounds, in some instances in combination with other confounding factors, have been associated with an increased incidence of liver cancers or chronic liver damage and diseases, as reviewed and discussed by Svirčev et al [12], and supported by recent findings [18][19][20]. Interestingly, epidemiologic studies have also linked chronic exposures to drinking water contaminated with cyanobacteria and their metabolites to the increased incidence of colorectal or small intestinal cancer in China [21], Portugal [22], and Serbia [12,23], or stomach cancer mortality in China [24].…”
mentioning
confidence: 82%
“…While the conventional treatment technologies can eliminate intact toxic cyanobacterial cells effectively, these technologies have limited capability for removal of dissolved cyanobacterial toxins, which allows that these reach human populations via drinking water supplies in sufficiently high concentrations to cause adverse effects in the gastrointestinal system (Table 1). Chronic exposures to drinking water contaminated with cyanobacterial compounds, in some instances in combination with other confounding factors, have been associated with an increased incidence of liver cancers or chronic liver damage and diseases, as reviewed and discussed by Svirčev et al [12], and supported by recent findings [18][19][20]. Interestingly, epidemiologic studies have also linked chronic exposures to drinking water contaminated with cyanobacteria and their metabolites to the increased incidence of colorectal or small intestinal cancer in China [21], Portugal [22], and Serbia [12,23], or stomach cancer mortality in China [24].…”
mentioning
confidence: 82%
“…Microcystinleucine arginine (LR) displays L-leucine and L-arginine at the two positions, respectively, and is the most abundant toxicant among microcystin variants. Microcystin-LR is broadly reported to pose a threat to aquatic animals and humans 20,21 .…”
Section: Introductionmentioning
confidence: 99%
“…We randomly selected 96 patients with HCC from our previous case-control study [12]. Liver tumor tissues were collected following surgery on patients diagnosed with HCC from Army Medical University hospitals.…”
Section: Hcc Patient Tumor Tissues and Mc-lr Exposure Testmentioning
confidence: 99%
“…However, controversy surrounds whether MC-LR can induce tumor formation. Although chronic low-dose MC-LR exposure did not increase the risk of developing tumors or induce tumors in animals [9], some data has indicated its tumorigenicity in cell lines [10,11] and our recent population study demonstrated a significant positive correlation between serum MC-LR levels and risk of hepatocellular carcinoma (HCC) [12]. Hence, the objective of this study was to elucidate the effects and mechanisms of MC-LR in tumor inducement in vitro and in vivo.…”
mentioning
confidence: 96%